Bioactivity Behaviour of Osteoblasts on Commercially Pure Titanium with TiO2-ZrO2 Nanocomposite Mixture Coating - Thekra Ismael Hamad; Rawaa Zaher Hassan Zwain; Ali Mohammad Ali Aljafery (Nano Biomedicine and Engineering, 2019)
This study aims to improve the bioactivity response of osteoblasts attachment and proliferation on commercial pure titanium surface by the mixture of nanocomposite coating material of 70% TiO2 (rutile 10-30 nm, Sky Spring Nanomaterials, USA) and 30% ZrO2 (20-30 nm, Sky Spring Nanomaterials, USA). This may increase the likelihood of developing the modified implant surface by electrophoretic deposition and the dipping methods of nanocomposite mixture to enhance the surface bioactivity and promote bone formation. Three groups of commercially pure titanium: one uncoated group and two coated groups with nanocomposite mixture of different coating techniques; one group for electro photic deposition technique (EPD); and one group for dip technique. The bioactivity evaluation of cell cultures, isolation of osteoblast cells from calvaria and long limbs of 3-4 days neonatal rats to evaluate the attachment and the proliferation assay in 4 and 8 days of incubation periods for each group. However, osteoblast cells attachment and proliferation showed the least attached and proliferated cells in uncoated samples, while the EPD coated sample showed the highest.